THE VAGINAL EXFOLIATIVE CYTOLOGY OF AWASSI EWES DURING POST-PARTURIENT PERIOD - Hussin, Amer M. (The Iraqi Journal of Veterinary Medicine, 2006)
This trail was carried out on twelve Awassi ewes in the Animal Farm of College of Veterinary Medicine in June 2005 to study the cellular changes that occur in the vaginal epithelium after parturition, by using vaginal smear method. The post-parturient period was divided into three periods; 4th, 16th and 28th days after parturition. Each period presented different sizes of vaginal epithelial cells, some of them were predominant. Keratinization takes place in all periods. The 2nd period was characterized by cellular division, presence of vacuolated epithelial cells and WBCs mainly neutrophils cells. The conclusion, variations in the vaginal epithelium may relate to the physiological status and the hormonal activity of the animals.